Apricot cultivars approved for production in Chelyabinsk Province - F. M. Gasymov (Труды по прикладной ботанике, генетике и селекции)
Background. The life in an industrial region, with hard labor and harmful emissions from enterprises, is far from healthy, so high-quality and vitamin-rich diets are needed. Apricot fruits are considered among the most beneficial for human health, due to their high nutritional value, rich biochemical composition, and diverse vitamin content. They are consumed fresh or processed into juices, fruit drinks, jams, candies or dried fruits. One of the ways to meet the demand for fresh fruits is to introduce apricot cultivars adapted to local conditions.Materials and methods. The study was targeted at local and introduced apricot cultivars planted in 2008–2009. Conventional methods were applied to assess them for winter hardiness and yield in 2020–2023. The analysis of variance with Microsoft Excel was used for statistical processing of the results.Results and conclusion. The results of apricot breeding and variety studies under the conditions of Chelyabinsk Province are analyzed. In the framework of the apricot breeding program launched in the Southern Urals, the breeding sources and cultivars from the collection of the South Ural Research Institute of Horticulture and Potato Growing were tested to assess their winter hardiness and yield potential. As a result of breeding efforts, new adaptable apricot cultivars ‘Uralets’ and ‘Prizer’ were released and included in the State Register for Selection Achievements Admitted for Usage in 2022 and 2023, respectively. The economic indicators of these cultivars (profitability ratios are 220.2% for ‘Uralets’ and 233.9% for ‘Prizer’) witness to their suitability for both commercial and amateur cultivation in Chelyabinsk Province.